A no throw-away vacation. - Dempsey, Mary A. (Americas)
Comments on the work of Stanley Selengut, who has built a vacation villa made entirely out of recycled and reusable products. Building of his vacation lodge on the island of St. John; The Caribbean and concerns about the wastes left behind by vacationers; Results of a workshop on sustainable development; Harmony; More.